Effects of acid-sensing ion channel-1A (ASIC1A) on cocaine-induced synaptic adaptations - Gupta, Subhash C.; Taugher-Hebl, Rebecca J.; Hardie, Jason B.; Fan, Rong; LaLumiere, Ryan T.; Wemmie, John A. (Frontiers in Physiology, 2023)
Chronic drug abuse is thought to induce synaptic changes in nucleus accumbens medium spiny neurons (MSNs) that promote subsequent craving and drug-seeking behavior. Accumulating data suggest acid-sensing ion channels (ASICs) may play a critical role. In drug naïve mice, disrupting the ASIC1A subunit produced a variety of synaptic changes reminiscent of wild-type mice following cocaine withdrawal, including increased AMPAR/NMDAR ratio, increased AMPAR rectification, and increased dendrite spine density. Importantly, these changes in Asic1a–/– mice were normalized by a single dose of cocaine. Here we sought to understand the temporal effects of cocaine exposure in Asic1a–/– mice and the cellular site of ASIC1A action. Six hours after cocaine exposure, there was no effect. However, 15hrs, 24 hrs and 4 days after cocaine exposure there was a significant reduction in AMPAR/NMDAR ratio in Asic1a-/- mice. Within 7 days the AMPAR/NMDAR ratio had returned to baseline levels. Cocaine-evoked changes in AMPAR rectification and dendritic spine density followed a similar time course with significant reductions in rectification and dendritic spines 24 hrs after cocaine exposure in Asic1a–/– mice. To test the cellular site of ASIC1A action on these responses, we disrupted ASIC1A specifically in a subpopulation of MSNs. We found that effects of ASIC1A disruption were cell autonomous and restricted to neurons in which the channels are disrupted. We further tested whether ASIC1A disruption differentially affects MSNs subtypes and found AMPAR/NMDAR ratio was elevated in dopamine receptor 1-expressing MSNs, suggesting a preferential effect for these cells. Finally, we tested if protein synthesis was involved in synaptic adaptations that occurred after ASIC1A disruption, and found the protein synthesis inhibitor anisomycin normalized AMPAR-rectification and AMPAR/NMDAR ratio in drug-naïve Asic1a-/- mice to control levels, observed in wild-type mice. Together, these results provide valuable mechanistic insight into the effects of ASICs on synaptic plasticity and drug-induced effects and raise the possibility that ASIC1A might be therapeutically manipulated to oppose drug-induced synaptic changes and behavior.